Evaluation of the elastic Young’s modulus and cytotoxicity variations in fibroblasts exposed to carbon-based nanomaterials - Homero F. Pastrana; Alexander X. Cartagena-Rivera; Arvind Raman; Alba Ávila (Journal of Nanobiotechnology, 2019)
Abstract Background The conventional approaches to assess the potential cytotoxic effects of nanomaterials (NMs) mainly rely on in vitro biochemical assays. These assays are strongly dependent on the properties of the nanomaterials, for example; specific surface area (SSA), size, surface defects, and surface charge, and the host response. The NMs properties can also interfere with the reagents of the biochemical and optical assays leading to skewed interpretations and ambiguous results related to the NMs toxicity. Here, we proposed a structured approach for cytotoxicity assessment complemented with cells’ mechanical responses represented as the variations of elastic Young’s modulus in conjunction with conventional biochemical tests. Monitoring the mechanical properties responses at various times allowed understanding the effects of NMs to the filamentous actin cytoskeleton. The elastic Young’s modulus was estimated from the force volume maps using an atomic force microscope (AFM). Results Our results show a significant decrease on Young’s modulus, ~ 20%, in cells exposed to low concentrations of graphene flakes (GF), ~ 10% decrease for cells exposed to low concentrations of multiwalled carbon nanotubes (MWCNTs) than the control cells. These considerable changes were directly correlated to the disruption of the cytoskeleton actin fibers. The length of the actin fibers in cells exposed to GF was 50% shorter than the fibers of the cells exposed to MWCNT. Applying both conventional biochemical approach and cells mechanics, we were able to detect differences in the actin networks induced by MWCNT inside the cells and GF outside the cell’s membrane. These results contrast with the conventional live/dead assay where we obtained viabilities greater than 80% after 24 h; while the elasticity dramatically decreased suggesting a fast-metabolic stress generation. Conclusions We confirmed the production of radical oxygen species (ROS) on cells exposed to CBNs, which is related to the disruption of the cytoskeleton. Altogether, the changes in mechanical properties and the length of F-actin fibers confirmed that disruption of the F-actin cytoskeleton is a major consequence of cellular toxicity. We evidenced the importance of not just nanomaterials properties but also the effect of the location to assess the cytotoxic effects of nanomaterials.